Evaluation of microhardness and color stability in PMMA and BIS-acryl as provisional restorative materials: A clinical study - Nivedita Sinha (Bioinformation, 2026)
Selecting provisional materials when esthetics and short-term mechanical stability are priorities remains a tedious task for clinicians. Therefore, it is of interest to compare the microhardness and colour stability of four common provisional materials (DPI, Trulon, Protemp and Cooltemp). Eighty specimens of PMMA and bis-acryl were fabricated each. Results showed that Protemp had the best overall performance among the tested materials. Thus, turmeric is a stronger colourant than coffee and Cooltemp showed the highest ΔE values.